Dividend announcements reconsidered dividend changes versus dividend surprises - Christian Andres; André Betzer; Inga van den Bongard; Christian Haesner; Erik Thiessen (University of Wuppertal, Schumpeter School of Business and Economics, 2011)
This paper reconsiders the issue of share price reactions to dividend announcements. Previous papers rely almost exclusively on a naive dividend model in which the dividend change is used as a proxy for the dividend surprise. We use the difference between the actual dividend and the analyst consensus forecast as obtained from I/B/E/S as a proxy for the dividend surprise. Using data from Germany, we find significant share price reactions after dividend announcements. Once we control for analysts' expectations, the dividend change loses explanatory power. Our results thus suggest that the naive model should be abandoned. We use panel methods to analyze the determinants of the share price reactions. We find (weak) support in favor of the dividend signaling hypothesis and no support for either the free cash flow hypothesis or the rent extraction hypothesis.
urn:nbn:de:hbz:468-20111011-111244-7
Keywords: G35; G34; 330; Dividend Announcements; Market Efficiency; Ownership Structure; Agency Theory; Dividende; Ankündigungseffekt; Signalling; Börsenkurs; Schätzung; Deutschland